Spatio-temporal ultrawideband indoor propagation modelling by reduced complexity geometric optics - Malik, W; Stevens, C; Edwards, D (2007)
A simple and efficient virtual-source ray-tracing technique for the simulation of indoor wideband radio and optical propagation channels is proposed. The parametric deterministic model considers the room geometry, transceiver locations, material properties and probe signal types. It is applied to the indoor ultrawideband channel in the FCC-allocated 3.1-10.6 GHz band, and a range of novel results are presented to illustrate several possible applications. The channel small-scale fading statistics and spatial variability are examined by synthesising a densely sampled aperture. Multiple-antenna array systems are simulated to evaluate multiple-input multiple-output performance. The multipath angular characteristics are analysed from the simulated azimuth-delay profile. The simulation results closely match previous channel measurement studies and statistical models, validating the proposed technique. It is shown that specular reflection is dominant, and power convergence is achieved with three reflections in a typical indoor environment. Thus, it is demonstrated that despite its simplicity, the model yields reliable and accurate results, and can therefore be a useful tool for indoor wireless network planning and performance prediction. © The Institution of Engineering and Technology 2007.